Betrayal in international buyer-seller relationships: Its drivers and performance implications - Leonidou, Leonidas C.; Aykol, Bilge; Fotiadis, Thomas A.; Christodoulides, Paul; Zeriti, Athina (My University, 2017)
Although betrayal is a common phenomenon in inter-organizational cross-border relationships, the pertinent literature has remained relatively silent as regards its examination. However, the effects of betrayal are both long-lasting and destructive, and therefore an in-depth investigation of the factors that are driving it, as well as its performance outcomes, is considered necessary. Using a sample of 262 exporters, we confirm that betrayal in their relationships with foreign buyers is significantly and positively affected by relational uncertainty, opportunism, inter-partner incompatibility, relational distance, and conflict. The harmful effect of most of these factors on betrayal becomes stronger in the case of high foreign environmental uncertainty and high foreign market dynamism. The importer’s betrayal actions are in turn responsible for reducing relational performance. In fact, this negative association between importer’s betrayal and relational performance is more evident in relationships characterized by low dependence levels and low degrees of tolerance by the exporter.
Keywords: Relational performance; Social exchange theory; Betrayal; Exporting; Exporter-importer relationships